2022
DOI: 10.1227/neu.0000000000002165
|View full text |Cite
|
Sign up to set email alerts
|

Does a Screening Trial for Spinal Cord Stimulation in Patients With Chronic Pain of Neuropathic Origin Have Clinical Utility (TRIAL-STIM)? 36-Month Results From a Randomized Controlled Trial

Abstract: BACKGROUND: Screening trials before full implantation of a spinal cord stimulation device are recommended by clinical guidelines and regulators, although there is limited evidence for their use. The TRIAL-STIM study showed that a screening trial strategy does not provide superior patient pain outcome at 6-month follow-up compared with not doing a screening trial and that it was not cost-effective. OBJECTIVE: To report the long-term follow-up results of the TRIAL-STIM study. METHODS: The primary outcome of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…In their study of patients undergoing a screening trial followed by OL-SCS implant versus going directly to OL-SCS implant, Eldabe et al reported clinically important reductions in pain intensity and EQ-5D at 36 months for both groups. 25 A ≥50% reduction in pain was observed for 33% (21/66) of the patients at 36 months. In the Eldabe et al study, different types of OL-SCS were used; the mean change in pain intensity measured on a Numerical Rating Scale from baseline was −2.80 for paresthetic stimulation, −1.87 for high-frequency stimulation and −2.04 for burst stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…In their study of patients undergoing a screening trial followed by OL-SCS implant versus going directly to OL-SCS implant, Eldabe et al reported clinically important reductions in pain intensity and EQ-5D at 36 months for both groups. 25 A ≥50% reduction in pain was observed for 33% (21/66) of the patients at 36 months. In the Eldabe et al study, different types of OL-SCS were used; the mean change in pain intensity measured on a Numerical Rating Scale from baseline was −2.80 for paresthetic stimulation, −1.87 for high-frequency stimulation and −2.04 for burst stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…20 More recently, others have advocated for no trial because there was no difference in numerical rating scale scores at 36 months between patients with and without a trial. 21 Reimbursement rates of trials and different economic models across the globe will likely play a role in the debate and ultimate decision. Of note, although most trials are percutaneous, in some cases where anatomy or previous surgery prevents percutaneous lead passage, a “buried” lead trial may be used.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Table 2 summarizes the evolution of trialing in SCS. [12][13][14][15][16][17][18][19][20][21][24][25][26] What is the Current Role of Neuromonitoring?…”
Section: Evolution Of Trial Usage In Scs Placementmentioning
confidence: 99%
“…The analysis in the current study of patients who completed the follow-up is consistent with other previous reports of SCS. [20][21][22][23][24]…”
Section: Original Researchmentioning
confidence: 99%